Pengaruh Kualitas Pelayanan SDM terhadap Kepuasan Pasien Pengguna Layanan Telemedicine - Dewi Agustina; Annisa Zahra; Aprillia Dwi Astuti; Sahkira Nabila Utami Siregar; Suci Ramadhani Rangkuti; Rabiatul Chazali; Ajeng Andini; Safira Zahara; Aulia Nazwa Fathurahmi; Mely Febriani; Amelia Putri Amanda; Sry Wulan Silaban; Audy Vimala Sari (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Telemedicine is a technology-based healthcare innovation that can improve access and efficiency. The quality of service provided by human resources (HR) plays a crucial role in determining patient satisfaction. This study aims to analyze the influence of HR service quality on patient satisfaction among telemedicine users. The method used was a literature review using a qualitative descriptive approach through analysis of scientific articles from various databases published between 2020 and 2025. The results indicate that HR service quality significantly influences patient satisfaction, particularly through aspects of reliability, responsiveness, assurance, empathy, and effective communication. Patient satisfaction is also influenced by ease of access, time efficiency, and trust in the services provided. However, limitations such as the lack of in-person physical examinations remain a challenge in the implementation of telemedicine. Therefore, improving HR competency, particularly in digital communication and technology utilization, is essential to improving the quality of telemedicine services. Therefore, HR service quality is a key factor in increasing patient satisfaction and the successful development of digital healthcare services.